Iodine contrast-to-noise ratio improvement at unit dose and contrast media volume reduction in whole-body photon-counting CT. Issue 126 (May 2020) - Sawall, S.; Klein, L.; Amato, C.; Wehrse, E.; Dorn, S.; Maier, J.; Heinze, S.; Schlemmer, H.-P.; Ziener, C.H.; Uhrig, M.; Kachelrieß, M.
Highlights: All patients benefit from the favorable properties of photon-counting CT detectors. Photon-counting CT will allow for a radiation dose reduction of up to 46 %. Patients will benefit from a reduction of administered contrast media volume. Abstract: Purpose: To assess the dose-normalized iodine contrast-to-noise-ratio (CNRD) improvement and contrast media reduction potential obtained with photon-counting (PC) CT compared to conventional energy-integrating (EI) CT as a function of patient size and tube voltage. Method: Images of a semi-anthropomorphic phantom of different sizes (small, medium, large) equipped with vials containing different iodine concentrations were acquired at the SOMATOM CounT prototype CT system using tube voltages of 80 kV–140 kV. CNRD is evaluated in reconstructions obtained using the EI detector, the PC detector using a single bin, and in reconstructions obtained by statistically optimally weighting acquisitions with two bins. Iodine CNRD improvements, potential dose reduction and the potential contrast media volume reduction are reported. Results: In general, iodine CNRD improvement increases with increasing tube voltage for all patient sizes. In particular, if only one energy bin is used, the CNRD improvement is up to 30 % (small: 10 %, medium: 18 %, large: 30 %) and up to 37 % if an optimal weighting of two bins is performed (small: 13 %, medium: 25 %, large: 37 %) which is equivalent to the potential contrast media volume reduction. The improved iodine CNRD of PC compared to EI may allow for a potential radiation dose reduction of up to 46 %. Conclusions: All patients' iodine contrast at given x-ray dose, and particularly medium and large sized patients acquired at higher tube voltages, may benefit from photon-counting CT. The iodine contrast improvement can be used to reduce patient dose or to reduce the amount of contrast agent that is administered.